ETHNOLINGUISTICS AND MODERNITY - Khamidova Mahbuba Kakhkharovna (Лучшие интеллектуальные исследования, 2023)
Annotation: The article is an overview of the current state of ethnolinguistic research and its relevance in the modern world. The article also highlights the importance of ethnolinguistics in understanding cultural diversity and preserving linguistic heritage.